PENGARUH FAKTOR BUDAYA, SOSIAL, PRIBADI DAN PSIKOLOGIS TERHADAP KEPUTUSAN BELI MAHASISWA PADA PRODUK MIE INSTANT MEREK INDOMI - Sasnelwati, Sasnelwati (Jurnal Ekobistek, 2013)
Abstract - The aims of the research is determine how big the Cultural Factors, Social, Personal And Pikologis Buy Decisions Affecting Students Against Product brand Indomie Instant Noodles . The research only for the Student UPI YPTK . In the research that is culturally variable (X1) , social (X2) personal (X3) psychological (X4) and the decision to buy (Y) by using the method of data collection through surveys and questionnaires circulated, with a sample of 80 respondents. analytical methods used were correlation analysis and regression analysis. Used to test the hypothesis that significant test 0.00 <0.05. The results showed the influence of culture (X1), social (X2) personal (X3) psychological (X4) and the decision to buy (Y), amounting to 82.2% with a significant R2 0.00 <0.05. partially no significant influence between cultures with purchasing decisions where cultural factors have a t value <t table (-1.968 <1.986) with a significant level of 0.052> 0.05, social factors (X2) significantly influence the purchasing decision (Y) , characterized by the value of t count> t table (4.154> 1.992) with a significant level of 0.000> 0.05. personal factors (X3) significantly influence the purchasing decision (Y) is characterized by private (X3) has t count> t table (13.891> 1.992) with a significant level 0.002 <0.05, psychology (X4) does not significantly influence the purchase decision (Y) is characterized by psychology (X4) have t <t table (-0.574 <1.992) with a significant level of 0.567> 0.05,. There jointly influence the cultural, social, personal and psychological to the purchasing decision because the calculated F value of 86.693 with the F table at 2,338 so F count> F table 86.693> 2.338 with significant 0.000 <0.05, then Ho is rejected. That is, the multiple linear regression equation is: Y = 1.790 to 0.135 +0.247 x_1 + x_2 0,879 X_3-0, 040 X_4. If the variable cultural, social, personal and psychological equal to zero (0), then the decision to buy at 1,790. Finally the authors recommend to Indomie Instant Noodles expected to pay more attention to other factors that could affect the handling of cultural and psychological, such as taste and innovation in order to increase for the foreseeable future. Keywords: Factor Cultur, Social, Personal Psychology, Results Buy